Archaeological restitution between the multiplicity of concepts and methods of application and objectives - bakar, Kamal; beldjouzi, bouabdellah (The Algerian Historical Journal, 2026)
The archaeological heritage generated a set of studies and hypotheses, especially those that we lost the historical texts that were not documented historically, suffered from vandalism and damage to their condition, especially in archaeological sites, whether due to the large number of visitors, as well as wars and hostilities, the black market for antiquities, and natural disasters prompts us to re-evaluate and study this heritage by applying the approach of archaeological reimagining of archaeological sites. Through the reconstitution of archaeological sites by different ways, methods and forms, which has recently developed with the modernity of architectural survey and data processing with advanced technology, it could be printed in the form of three-dimensional objects, and the challenge will be to determine the correct method and appropriate application, as our topic will be this contribution to how it works, down to understanding and classifying it in order to re-display the archaeological heritage in a new way. re-employ and exploit it.